2013
DOI: 10.1111/j.1728-4465.2013.00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Decline in Intimate Partner Violence Against Women in Bangladesh: Qualitative Evidence

Abstract: The Bangladesh government, nongovernmental organizations, donors, and advocacy groups have attempted various interventions to promote gender equality and reduce intimate partner violence (IPV) against women, but rigorous evaluations of these interventions are rare and few published studies have yet to show that any of them has had a substantial impact. This study presents qualitative evidence from four villages in central and northern Bangladesh drawn from 11 group discussions (6 with men, 5 with women), 16 op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…In such a household, younger CMW is not only subordinate to men, but also to senior women in the family; despite education levels, at the bottom of the rung, they are more vulnerable to MIPPV. However, a recent qualitative study, conducted in four Bangladeshi villages where MIPPV is declining, revealed that younger CMW, when educated and employed, no longer occupy a lower status than older women in the family (Schuler, Lenzi, Nazneen, & Bates, 2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In such a household, younger CMW is not only subordinate to men, but also to senior women in the family; despite education levels, at the bottom of the rung, they are more vulnerable to MIPPV. However, a recent qualitative study, conducted in four Bangladeshi villages where MIPPV is declining, revealed that younger CMW, when educated and employed, no longer occupy a lower status than older women in the family (Schuler, Lenzi, Nazneen, & Bates, 2013).…”
Section: Discussionmentioning
confidence: 98%
“…However, if men in poor households, which are fertile ground for conflict over limited resources, feel threatened by women's power, then they may resort to backlash and violence (Chin, 2012). Women in the beginning stages of empowerment may also not have the necessary resources to fend off violence (Schuler et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Several decades ago, researchers noted that men often failed to adhere to the patriarchal norm that defined men as providers (Cain, Khanam, & Nahar, 1979); this was still a common source of marital conflict in the1990s, and defensiveness and conflict over this failure often provoked men to abuse their wives (Schuler, Lenzi, Nazneen, & Bates, 2013) Village D is notable because, more than in the other villages, women tend to adhere to traditional gender norms both in their behavior and in the narratives surrounding their behavior. Perhaps because extreme poverty was virtually nonexistent and men were able to actualize the norm of husband as provider, rates of IPV were relatively low despite the low level of empowerment of women.…”
Section: Discussionmentioning
confidence: 99%
“…The field research team reviewed the findings and conclusions and discussed them with the lead author, who further revised them. Results were also triangulated with findings from 13 focus groups and 74 life history narratives with women from the same villages (findings reported in Schuler et al 2013, 2016). …”
Section: Methodsmentioning
confidence: 99%
“…When feminine norms evolve (e.g., in response to expanded educational and employment opportunities for girls and women, and laws and policies supporting women’s equal rights and social participation), masculine norms may evolve to accommodate greater gender equity, or they may be thrown into crisis. In the former case, men may establish more collaborative, companionate and collegial relationships with their wives, help with housework, and/or change their routines to accommodate their wives’ income-generating activities (Schuler et al 2013). Alternatively, men may draw upon existing paradigms of hegemonic masculinity, view women’s empowerment—their acquisition of resources, agency and ability to make strategic life choices in the context of gender inequality (Malhotra and Schuler 2005)—as transgressive of social norms, feel that their masculine identities are being challenged, and respond with hostility and violence.…”
Section: Introductionmentioning
confidence: 99%